HUBUNGAN KARAKTERISTIK ISTRI, KARAKTERISTIK SUAMI DAN KARAKTERISTIK WILAYAH DENGAN KEMISKINAN RUMAH TANGGA DI KALIMANTAN SELATAN - Norma Yuni Kartika (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2018)
The goal of this paper is to review the characteristic of household poverty is South Kalimantan. This research is an analysis of secondary data sourced from the result of Indonesian Demographic and Health Survey (SDKI in Indonesia) in 2012, with 910 respondents of women who married were they are 15-49 years old who is still a couple as husband and wife when this survey took place. Analyzed using logistic regression test which using Software Statistical Package Social Science. Found that wife who didn’t finish their nine years basic education, with their first age marriage under 18 years old and do not working 14,4% of them get risk for their household in poverty. Husband who didn’t finish their nine years basic education and difference of region’s characteristic 22,9% of them get risk for their household in poverty in South Kalimantan. Education improve ment for wife and husband both in rural or urban is a human resourch improvement and opportunities to compete for work, especially for women at once maturing their first age marriage in order their household can be free from poverty.